Wytrzymałość w treningu uzupełniającym szkolenie zasadnicze jeźdźca = Endurance in training, supplementary basic training rider - Mrozkowiak, Mirosław (Journal of Education, Health and Sport, 2016)
Mrozkowiak Mirosław. Wytrzymałość w treningu uzupełniającym szkolenie zasadnicze jeźdźca = Endurance in training, supplementary basic training rider. Journal of Education, Health and Sport. 2016;6(5):55-76. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.51047 http://ojs.ukw.edu.pl/index.php/johs/article/view/3508 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.04.2016. Revised 25.04.2016. Accepted: 05.05.2016. Wytrzymałość w treningu uzupełniającym szkolenie zasadnicze jeźdźca Endurance in training, supplementary basic training rider Mirosław Mrozkowiak Bioergonsport, Nowa Biała 8p, 09-411 Biała Mirosław Mrozkowiak Bioergonsport, Nowa Biała 8p, 09-411 Biała e-mail: magmar54@interia.pl strona: http://wadypostawy.republika.pl Słowa kluczowe: wytrzymałość, tętno, trening uzupełniający. Keywords: endurance, heart rate, training. Streszczenie Wstęp. Publikacji na temat kształtowania wytrzymałości u jeźdźców w dostępnej literaturze jest bardzo mało. W sporcie kwalifikowanym należy zająć się przygotowaniem do zawodów nie tylko konia ale również jeźdźca. Cel. Wykazanie skuteczności zastosowanego wysiłku fizycznego w doskonaleniu poziomu wytrzymałości ogólnej jeźdźców WKKW. Materiał i metodyka. Badania przeprowadzono na 10 zawodnikach wąskiej kadry jeźdźców WKKW podczas zgrupowania sportowo-rehabilitacyjnego. Wysiłek standardowy to bieg ciągły na dystansie 1 km w czasie 5 min. Pomiary tętna przeprowadzane były w pierwszych i ostatnich dniach zgrupowania po obciążeniu standardowym. Wyniki. Największe odchylenie stanowiące górną granicę w stosunku do wartości średniej tętna powysiłkowego posiada zawodnik nr 9: 30 uderzeń, a najmniejsze zawodnik nr 7: 25 uderzeń przy średniej 24,3. Żaden z zawodników podczas 1 i 2 pomiaru (10 i 20 sekunda) nie posiada wartości niższych od wartości średniej. Wnioski. Zmiany jakie zaszły pomiędzy 1 i 2 badaniem zwiększyły adaptacje organizmu do wysiłku wytrzymałościowego. Częstość pracy serca przy obciążeniu stosowanym podczas zgrupowania jest wielkością zmienną i indywidualną. Doskonalenie pracy układu sercowo- naczyniowego rozwinęła się u poszczególnych badanych indywidualnie. Należy obiektywnymi metodami badawczymi sprawdzić przydatność tego treningu wytrzymałości w jeździeckich zawodach sportowych. Abstract Introduction publications on shaping the endurance riders in the open literature is very little. In the sport of certified professional preparation should be addressed not only the horse but also a rider. Goal. To demonstrate the effectiveness of applied physical exertion in the improvement of the level of the overall strength of the three-day event riders. Material and methods. The study was conducted on 10 players a narrow cadre of eventing riders during rehabilitation and sports camps. The effort is a continuous run at standard 1 km at a time 5 min. Pulse Measurements are carried out in the first and last days of the grouping after the workload standard. The results. The largest deviation being the upper limit in relation to the average pulse rate after exercise has a player No 9:30 strokes, and the smallest player no. 7:25 strokes with an average 24.3. None of the players during the 1 and 2 (10 and 20 second) does not have a value lower than the value of the average. Conclusions. Changes that have taken place between 1 and 2 test increased adaptations to endurance exercise. Heart rate with a load of used when grouping is the size of the variable and the individual. Improvement of the work of the cardiovascular system has evolved in each test individually. You need objective research methods to check the usefulness of the training in equestrian sports competitions.